PENGARUH BRAND EQUITY TERHADAP PENJUALAN, PROFITABILITAS, DAN PERTUMBUHAN PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Mutiara Hisanah Harahap; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effect of brand equity on sales and financial performance. The independent variable namely brand equity is measured by a perpetuity perspective. The first dependent variable is that sales are measured by the results of year-end sales. Furthermore, for the second dependent variable, profitability is measured from the NPM ratio. The final dependent variable is that growth will be measured by total asset growth.The population in this study consisted of four sub-sectors of the company, namely companies in the food and beverage, cosmetics, transportation and hotel sub-sectors, which were listed on the Stock Exchange in 2013-2017. The sampling method in this study was purposive sampling. The criteria for companies are food and beverage, cosmetics, transportation and hotel sub-sector companies, and companies must have complete data and support research. The number of samples in this study is 145 data and the analysis technique used is OLS regression. The empirical results from this study indicate that brand equity affects sales. But on the contrary, brand equity has no effect on both profitability and company growth.